A rare clinical presentation of Desmoplastic Trichilemmoma mimicking Invasive Carcinoma - Daniela Tiemi Sano; Jeane Jeong Hoon Yang; Antonio José Tebcherani; Luiz Arthur de Paula Machado Bazzo (Sociedade Brasileira de Dermatologia, 2014)
Trichilemmoma is a benign neoplasm from the outer sheath of the pilosebaceous follicle. Desmoplastic trichilemmoma, a rare variant, is histologically characterized by a central area of desmoplasia that can clinically mimic an invasive carcinoma, requiring histopathological examination to define the diagnosis.